Remaining Nameless: Names, Hiding, and Dislocation Among Delhi’s Runaways - Jonah Steinberg (South Asia Multidisciplinary Academic Journal)
In India, child runaways inhabiting urban space mobilize a complex set of naming strategies—both for themselves as individuals and for the category of person to which they see themselves belonging—as a component of strategies of evasion, dissimulation, and self-protection. In this widely-replicated mode of narrative praxis, iterated in similar ways throughout the Subcontinent (and beyond), personal names as deployed by ‘street children’ become fluid vehicles of strategic self-positioning to circumvent forms of power that seek to define, fix, and track the children. As any agent in public space threatens to temper their mobility and freedom, and potentially to make their location known to forces they wish to evade, these runaways may use dozens of names. The names are not used in unpatterned ways, but rather they are situationally-contingent.